2018
DOI: 10.1192/bjo.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative systematic review of barriers and facilitators to patient-involved antipsychotic prescribing

Abstract: BackgroundDespite policy and practice mandates for patient involvement, people with serious mental illness often feel marginalised in decisions about antipsychotic medication.AimsTo examine stakeholder perspectives of barriers and facilitators to involving people with serious mental illness in antipsychotic prescribing decisions.MethodSystematic thematic synthesis.ResultsSynthesis of 29 studies identified the following key influences on involvement: patient's capability, desire and expectation for involvement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
(394 reference statements)
2
16
0
Order By: Relevance
“…Our findings identify the perceived value of sharing concerns and enhancing support in FI amongst both YP and family members, and similarly this accords with a substantial body of literature exploring family and carer experiences of family involvement in adult psychosis treatment [ 23 , 24 ]. A review of 22 qualitative studies identified the key elements of FI as therapeutic alliance, support, and the opportunity for sharing, along with the provision of psychoeducation around psychosis [14] , and each of these factors is evident in our findings.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings identify the perceived value of sharing concerns and enhancing support in FI amongst both YP and family members, and similarly this accords with a substantial body of literature exploring family and carer experiences of family involvement in adult psychosis treatment [ 23 , 24 ]. A review of 22 qualitative studies identified the key elements of FI as therapeutic alliance, support, and the opportunity for sharing, along with the provision of psychoeducation around psychosis [14] , and each of these factors is evident in our findings.…”
Section: Discussionsupporting
confidence: 81%
“…Findings from qualitative adult studies are therefore needed for interpretation. In line with the present study, qualitative research has previously reported that prescribers commonly view AP as the primary or key treatment for psychosis [ 9 , 10 ]; as Shephard et al argue [10] , such views are likely to influence how information and treatment offers are presented to patients.…”
Section: Discussionsupporting
confidence: 80%
“…Clinicians’ preference for combined treatment closely accorded with family members’ views, and to a moderate degree with those of YP. Previous qualitative studies have compared views of psychosis treatment between participant groups, but focus predominantly on aspects of antipsychotic prescribing, and none discuss adolescent treatment [ 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, individuals experiencing severe mental health problems are often given little choice over the treatment options they receive [5][6][7][8]. Recent qualitative and survey-based studies with service users and health care staff have highlighted a number of factors that are barriers to the shared decision-making process, including perceptions regarding service user capability and capacity, aetiological beliefs, current risk to self and others, quality of research in the field, treatment costs and inadequate consultation times [9,10]. Such barriers exist despite evidence showing that shared decision-making and increased treatment choice is desired by both service users and health care staff alike [6,7,10,11] and can be beneficial for treatment-related empowerment [12] and personal recovery [13].…”
Section: Introductionmentioning
confidence: 99%